Differential Evaluating Effect on Exercise Capacity of Cardiopulmonary Exercise Testing and Treadmill Exercise Testing in Post-percutaneous Coronary Intervention Patients - Gao, Yifan; Feng, Bin; Hu, Rong; Zhang, YingYue; Shi, Yajun; Xu, Yong; Ma, Jing (Frontiers in Cardiovascular Medicine, 2021)
Background: Treadmill exercise testing (TET) is commonly used to measure exercise capacity. Studies have shown that cardiopulmonary exercise testing (CPET) is more accurate than TET and is, therefore, regarded as the “gold standard” for testing maximum exercise capacity and prescribing exercise plans. To date, no studies have reported the differences in exercise capacity after percutaneous coronary intervention (PCI) using the two methods or how to more accurately measure exercise capacity based on the results of TET. Aims: This study aims to measure maximum exercise capacity in post-PCI patients and to recommend exercise intensities that ensure safe levels of exercise. Methods: We enrolled 41 post-PCI patients who were admitted to the Cardiac Rehabilitation Clinic at the First Medical Center, the Chinese PLA General Hospital, from July 2015 to June 2016. They completed CPET and TET. The paired sample t-test was used to compare differences in measured exercise capacity, and multiple linear regression was applied to analyze the factors that affected the difference. Results: The mean maximum exercise capacity measured by TET was 8.89 ± 1.53 metabolic equivalents (METs), and that measured by CPET was 5.19 ± 1.23 METs. The difference between them was statistically significant (p = 0.000) according to the paired sample t-test. The difference averaged 40.15% ± 2.61% of the exercise capacity measured by TET multiple linear regression analysis showed that the difference negatively correlated with waist-hip ratio (WHR). Conclusion: For the purpose of formulating more accurate exercise prescription, the results of TET should be appropriately adjusted when applied to exercise capacity assessment. Clinical Trial Registration:http://www.chictr.org.cn/ number, ChiCTR2000031543.